2020
DOI: 10.1167/iovs.61.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adult Neural Retina Extracellular Vesicle Release, RNA Transport and Proteomic Cargo

Abstract: Citation: Mighty J, Zhou J, Benito-Martin A, et al. Analysis of adult neural retina extracellular vesicle release, RNA transport and proteomic cargo. Invest Ophthalmol Vis Sci. 2020;61(2):30. https://doi.org/10.1167/iovs.61.2.30 PURPOSE. Extracellular vesicles (EVs) contain RNA and protein cargo reflective of the genotype and phenotype of the releasing cell of origin. Adult neural retina EV release, RNA transfer, and proteomic cargo are the focus of this study. METHODS. Adult wild-type mouse retinae were cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…This aligns with our recent findings showing that mRNA and miRNA are packed into retinal progenitor cell EVs, and the content is functional following transfer to target retinal cells [34]. Additional recent work suggests that EV transfer of genetic material occurs between differentiated adult neural retina and multipotent retinal progenitor cells [20]. In this study, early differentiating 3D retinal organoid EVs were uptaken into multipotent hRPCs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This aligns with our recent findings showing that mRNA and miRNA are packed into retinal progenitor cell EVs, and the content is functional following transfer to target retinal cells [34]. Additional recent work suggests that EV transfer of genetic material occurs between differentiated adult neural retina and multipotent retinal progenitor cells [20]. In this study, early differentiating 3D retinal organoid EVs were uptaken into multipotent hRPCs.…”
Section: Discussionsupporting
confidence: 91%
“…Both, 3D retinal organoids and EVs were confirmed to contain the 6 selected miRNAs ( Figure 6A). To demonstrate cell-to-cell cargo transfer by EVs released from retinal organoids, we labeled EV RNA with the green (FITC) fluorescent dye Syto RNASelect and, EV lipid envelopes with red (TRITC) fluorescent dye PKH26, and performed live imaging on their uptake into non-labeled human retinal progenitor cells (hRPCs) [20,21]. Following 15 hours of co-incubation of unlabeled hRPCs and fluorescently labeled EVs, media was replaced with fresh media without labeled EVs to quantify uptake, retention and reduction of EV-transferred RNA in hRPCs.…”
Section: Confirmation Of Ev Mirna Cargo and Ev-mediated Rna Transfer mentioning
confidence: 99%
“…6 A). To demonstrate cell-to-cell cargo transfer by EVs released from retinal organoids, we labeled EV RNA with the green (FITC) fluorescent dye Syto RNASelect and, EV lipid envelopes with red (TRITC) fluorescent dye PKH26, and performed live imaging on their uptake into non-labeled human retinal progenitor cells (hRPCs) 20 , 21 . Following 15 hours of co-incubation of unlabeled hRPCs and fluorescently labeled EVs, media was replaced with fresh media without labeled EVs to quantify uptake, retention and reduction of EV-transferred RNA in hRPCs.…”
Section: Resultsmentioning
confidence: 99%
“…This feature makes these vesicles very interesting candidates as biomarkers and therapeutic drug delivery systems for a variety of chronic diseases, including cancer and degenerative diseases, such as DR [59]. A recent study characterized the EVs released by adult neural retina in culture and this allowed to determine the cellular origin of different types of EVs through the analysis of their molecular cargo (RNA and proteins) [60]. The authors were able to detect EVs derived from photoreceptors which contain proteins such as rhodopsin, the photo-responsive receptor of rod cells, and cadherin related family member 1 (Cdhr1), an adhesion protein that is normally present in the outer and inner segments of photoreceptors.…”
Section: Crosstalk Between Endothelial Cells and Other Retinal Cells mentioning
confidence: 99%
“…They have also detected the presence of neuronal-specific nuclear protein (NeuN) in the isolated EVs, a marker for amacrine and retinal ganglion cells. Additionally, through their molecular content, they were able to conclude that the retinal-derived EVs are mainly related with processes such as phototransduction, synapse structure, RNA processing, and transcription regulation [ 60 ]. Furthermore, other studies have also demonstrated that EVs from distinct retinal cells, such as astrocytes and retinal pigment epithelial (RPE) cells present different protein profiles, which suffer alterations during pathophysiological processes [ 61 , 62 ].…”
Section: Crosstalk Between Endothelial Cells and Other Retinal Celmentioning
confidence: 99%